Pharmacological Profile of 9,11-Dehydrocortexolone 17α-Butyrate (CB-03-04), a New Androgen Antagonist with Antigonadotropic Activity - Celasco, Giuseppe; Moro, Luigi; Bozzella, Roberta; Ferraboschi, Patrizia; Bartorelli, Luisa; Marco, Roberto Di; Quattrocchi, Cinzia; Nicoletti, Ferdinando (Arzneimittelforschung, 2005)
A series of new cortexolone-related derivatives has been synthesized and investigated for potential anti-androgenic activity. Among the steroids evaluated, 9,11-dehydrocortexolone 17a-butyrate (CB-03-04) was the most promising one. The compound displayed a strong local anti-androgenic activity in hamster’s flank organ test, and it was also found to be effective in the rat after subcutaneous injection. When compared to other well known androgen antagonists, the rank order of topical anti-androgenic activity in that test was: cyproterone acetate (CAS 427-51-0) ≥ CB-03-04 > finasteride (CAS 98319-26-7) > flutamide (CAS 13311-84-7). In addition, the steroid had selective antigonadotropic activity, when injected into parabiotic rats, and was about as active as progesterone. The activity of CB-03-04 was ascribed mainly to its ability to compete with the stimulating effects of testosterone and dihydrotestosterone and, concurrently, to inhibit the gonadotropins hypersecretion. This bimodal mechanism of action could be predictive for the clinical usefulness of the steroid in the treatment of prostate cancer and benign prostate hypertrophy.
Keywords: Antiandrogens; CB-03-04; Cyproterone acetate; 9,11-Dehydrocortexolone 17α-butyrate, hamster, pharmacoligical profile, rat; Finasteride; Flutamide; Gonadotropin inhibitors